(3GdChQGb (B( (3aj CNHGQ Bd GdYHGS hCTYGQge (B)s - (3eMeO Hf jMji Hf YHO Gddg, CHh HcQ GdUhdj, hbO jYQa HGdTWQfLj,J (B335 (3g` s
(3ChdgG (B:s
(3bO YQafG hddg GdMeO ef PcQ CNHGQ GdbGgQ s
(3BNQgG (B:s
(3hbO Yde CejQ GdeDefjf s
(3QJHg Ydi MQha GdeYLes
(3ai CNHGQ GdNdaGA GdQGTOjf ef Hfi YHGSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B136 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B105s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B38 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs